1998
DOI: 10.1016/s0006-3495(98)77724-0
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Proton Currents by Methanol in a Dioxolane-Linked Gramicidin A Channel in Different Lipid Bilayers

Abstract: The mobility of protons in a dioxolane-linked gramicidin A channel (D1) is comparable to the mobility of protons in aqueous solutions (Cukierman, S., E. P. Quigley, and D. S. Crumrine. 1997. Biophys. J. 73:2489-2502). Aliphatic alcohols decrease the mobility of H+ in aqueous solutions. In this study, the effects of methanol on proton conduction through D1 channels were investigated in different lipid bilayers and at different HCl concentrations. Methanol attenuated H+ currents in a voltage-independent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
0
26
1
Order By: Relevance
“…For that we suggest that in the case of large single crystals the role of the water is to repair defects in the relatively fragile lattice, allowing the appearance of macroscopic long-range effects.. The Grotthuss mechanism can be applied to some extent to these systems, 24,25 where water in the supramolecular compounds can be aligned forming polarized chains leading to an additional cooperative mechanism of the conductivity properties due to the presence of polarized water molecules. Proton transfer can produce an electric current when these water molecules instantly connect their fragments through the matrix network, as a result of which preferential conductivity properties in the parallel orientation are observed.…”
Section: Thiourea-halogen Systemmentioning
confidence: 95%
“…For that we suggest that in the case of large single crystals the role of the water is to repair defects in the relatively fragile lattice, allowing the appearance of macroscopic long-range effects.. The Grotthuss mechanism can be applied to some extent to these systems, 24,25 where water in the supramolecular compounds can be aligned forming polarized chains leading to an additional cooperative mechanism of the conductivity properties due to the presence of polarized water molecules. Proton transfer can produce an electric current when these water molecules instantly connect their fragments through the matrix network, as a result of which preferential conductivity properties in the parallel orientation are observed.…”
Section: Thiourea-halogen Systemmentioning
confidence: 95%
“…In the top graph of figure 17, measurements of 1 M HCl conductivity (λ, green symbols) and g H in the SS channel (red symbols) have been plotted as a function of the concentration of methanol in solution (127). In the bottom graph, these measurements were normalized to the values of λ and g H in the absence of methanol.…”
Section: Blocking Proton Transfer: the Effects Of Methanol In Ga Chanmentioning
confidence: 99%
“…g H is considerably more attenuated than λ by methanol. The line connecting the g H points is based on a model in which one methanol molecule on average partitions inside the pore of the SS channels and 'blocks' I H (127). The basic mechanisms by which methanol attenuates proton transfer in gA channels remains elusive (85,129).…”
Section: Blocking Proton Transfer: the Effects Of Methanol In Ga Chanmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, proton transfer can be measured in a single channel molecule. Recent work from our laboratory (10)(11)(12)16,(22)(23)(24) have used the SS and RR diastereoisomers of dioxolane-linked gA channels (16,25) to measure H 1 transfer in water wires, and to correlate those experimental measurements with possible molecular mechanisms (16,26). It was suggested that the chiral centers of the dioxolane linker underlie the profound quantitative and qualitative differences in the rate of H 1 transfer in distinct gA channels.…”
Section: Introductionmentioning
confidence: 99%